(untitled) (Journal of Environmental Science and Natural Resources, 2019)
The present study was conducted to carry out a comparative study on farm materials (water, soil, feed) and the quality parameters of pangus (Pangasianodon hypophthalamus) of five different farms in Trishal area under Mymensingh district. The study was carried out during May-June, 2016. Most of the pangus farmers used homemade or farm made supplementary feeds for pangus culture The percent moisture, protein, lipid and ash content in fresh fish ranged from 77.05 to 78.79, 14.21 to14.84, 3.55 to 4.49 and 2.03 to 2.67 whereas after 24 hrs of death of fishes, these percent values changed as 77.05 to 78.79, 14.21 to14.84, 3.55 to 4.49 and 2.03 to 2.67. Slight changes observed in different quality parameters in the fish samples 24 hrs after death as dead fishes were preserved at chilling temperature in a homestead refrigerator till analysis. Therefore, the study could be concluded that- though the values for different parameters of farm materials (water, soil, feed) and quality parameters of fish samples differed but was mostly not significant. The differences observed in the parameters might be due to the variations in management techniques of each farm. J. Environ. Sci. & Natural Resources, 11(1-2): 109-119 2018